Mixed polyposis of the colon - Piñeyro, Alberto; Bergalli, Luis E; Navarrete, Héctor (Cirugía del Uruguay, 2000)
The authors present a clínica/ case of mixed colonic polyposis (hyperp/astic and adenomatous) associated to an important family history of co/orrectal cancer. Histochemical and epidemiological evidence is provided which suggests (at /east occasionally) the transformation of hyperplastic and hamartomatous polyps into neoplastic lesions. The authors conclude that it is necessary to revise and eventual/y modify the concept that hyperplastic and hamartomatous polyps are not premalignant and that no treatment is indicated.